Mesoporous sulfur-modified iron oxide as an effective Fenton-like catalyst for degradation of bisphenol A - Du, Jiangkun; Bao, Jianguo; Fu, Xiaoyan; Lu, Chenghang; Kim, Sang Hoon (ELSEVIER SCIENCE BV, 2016)
A mesoporous sulfur-modified iron oxide (MS-Fe) was prepared as a heterogeneous H2O2 catalyst for degradation of BPA. The physico-chemical properties of MS-Fe and bare M-Fe were characterized by BET surface area measurement, SEM, XRD, MIR and XPS. Both M-Fe and MS-Fe composites appeared as cubic microparticles with abundant pores and cracks as well as large surface area. As depicted by XRD, EDX and XPS, M-Fe is mainly consisted of hematite while MS-Fe is a kind of S-doped iron oxide with about 5-6% of sulfur element in terms of atomic ratio. In contrast to the poor catalytic activity of bare M-Fe, the MS Fe composites showed greatly improved efficiencies for H2O2 activation for BPA degradation. The high catalytic activity of this new Fenton-like catalyst can be obtained at different initial pH in range of 3.0-9.0. The time evolution of degradation of BPA followed pseudo-first-order kinetics, and the first-order rate constants showed a linear relationship with parameters of initial pH, catalyst dosage and concentration of BPA. However, the H2O2 dosage showed a dual effect on BPA degradation because excessive H2O2 addition lead to scavenging of hydroxyl radicals ((OH)-O-center dot). The investigation of working mechanisms of MS Fe suggested a synergistic effect of homogeneous and heterogeneous degradation reaction, wherein a strong acidic environment, abundant surface-bonded hydroxyl group and electron-mediating effect of sulfur all contributed to fast activation of H2O2. Overall, this new material overcomes the limitation of narrow working pH range and shows a fast oxidation of BPA with a low H2O2 and catalyst dosage, would have a good potential for environmental application. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: HYDROGEN-PEROXIDE; OXIDATIVE-DEGRADATION; EFFICIENT DEGRADATION; DOPED ALPHA-FE2O3; DECOMPOSITION; MECHANISM; NANOPARTICLES; CARBON; WATER; IONS